Effects of cuff width on arterial occlusion: implications for blood flow restricted exercise - Loenneke, Jeremy P.; Fahs, Christopher A.; Rossow, Lindy M.; Sherk, Vanessa D.; Thiebaud, Robert S.; Abe, Takashi; Bemben, Debra A.; Bemben, Michael G. (European journal of applied physiology, 2012)
The purpose of this study was to determine the difference in cuff pressure which occludes arterial blood flow for two different types of cuffs which are commonly used in blood flow restriction (BFR) research. Another purpose of the study was to determine what factors (i.e., leg size, blood pressure, and limb composition) should be accounted for when prescribing the restriction cuff pressure for this technique. One hundred and sixteen (53 males, 63 females) subjects visited the laboratory for one session of testing. Mid-thigh muscle (mCSA) and fat (fCSA) cross-sectional area of the right thigh were assessed using peripheral quantitative computed tomography. Following the mid-thigh scan, measurements of leg circumference, ankle brachial index, and brachial blood pressure were obtained. Finally, in a randomized order, arterial occlusion pressure was determined using both narrow and wide restriction cuffs applied to the most proximal portion of each leg. Significant differences were observed between cuff type and arterial occlusion (narrow: 235 (42) mmHg vs. wide: 144 (17) mmHg; p = 0.001, Cohen’s D = 2.52). Thigh circumference or mCSA/fCSA with ankle blood pressure, and diastolic blood pressure, explained the most variance in the cuff pressure required to occlude arterial flow. Wide BFR cuffs restrict arterial blood flow at a lower pressure than narrow BFR cuffs, suggesting that future studies account for the width of the cuff used. In addition, we have outlined models which indicate that restrictive cuff pressures should be largely based on thigh circumference and not on pressures previously used in the literature.